2019
DOI: 10.15407/ujpe64.8.665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Superstatistics on the Location of the Effective QCD Critical End Point

Abstract: Effects of the partial thermalization during the chiral symmetry restoration at the finite temperature and quark chemical potential are considered for the position of the critical end point in an effective description of the QCD phase diagram. We find that these effects cause the critical end point to be displaced toward larger values of the temperature and lower values of the quark chemical potential, as compared to the case where the system can be regarded as completely thermalized. These effects may be impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…( 5) it can be found that though σ for C ξ * v and T kin or T ef f are different, they both reflect the significant change of system event-by-event fluctuation. As in results from other models or data the enhancement structure of C v at low √ s N N shows the fluctuation of temperature extends to system size of all events in ensemble, the enhancement structure of C ξ * v 's kurtosis shows the fluctuation of C ξ * v behaves similarly [7,8,12], which indicates the unique properties of charged particles formed via parton phase are significantly different from those experienced no partonic process. Hence the energy dependence of C ξ * v with skewness and kurtosis could be alternative, significant and verifiable signal to investigate the nature around the critical point of hot dense matter created in heavy-ion collisions.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…( 5) it can be found that though σ for C ξ * v and T kin or T ef f are different, they both reflect the significant change of system event-by-event fluctuation. As in results from other models or data the enhancement structure of C v at low √ s N N shows the fluctuation of temperature extends to system size of all events in ensemble, the enhancement structure of C ξ * v 's kurtosis shows the fluctuation of C ξ * v behaves similarly [7,8,12], which indicates the unique properties of charged particles formed via parton phase are significantly different from those experienced no partonic process. Hence the energy dependence of C ξ * v with skewness and kurtosis could be alternative, significant and verifiable signal to investigate the nature around the critical point of hot dense matter created in heavy-ion collisions.…”
Section: Resultssupporting
confidence: 60%
“…Specific heat was carried out as one of the signals of phase transition in partonic level as well as nucleonic level and helps to inspect thermal properties of nuclear matter. In partonic level, the Lattice QCD predicted the phase transition as a crossover at zero baryon-chemical potential (µ B = 0) but while a first order phase transition could occur at finite baryonic density T c [7][8][9][10][11][12][13]. In nucleonic level, a liquid gas phase transition can occur at sub-saturation density and finite temperature [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%